Research Methodology Course for BSc 4th Year Nurses of Ad-din Women's Medical College through Medical Research Unit (MRU) (The Journal of Ad-din Women's Medical College, 2023)
Abstract not availableThe Journal of Ad-din Women's Medical College; Vol. 10 (1), Jan 2022; p 67-69